(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The figure of Julius Caesar, often criticized in the Renaissance, is worked out in Il Cesare, a tragedy of Orlando Pescetti (1594). The writer, who dedicates the work to Alfonso II, does not stage a hymn to the Republic or to the Empire, but an equidistant drama. Pescetti, in a continuous analogical reference to his present, shows the limits of Roman society and politics, characterized by the ambition of the Caesaricides, by the private interests of Marcus Anthony, by Caesar’s desire of power. La figura di Giulio Cesare, spesso criticata nel Rinascimento, viene ripresa nella tragedia Il Cesare di Orlando Pescetti (1594). Lo scrittore, che dedica l’opera ad Alfonso II, non porta in scena un inno alla repubblica o all’impero, bensì un dramma equidistante. Pescetti, in un continuo rinvio analogico al suo presente, mostra i limiti della società romana e della politica del tempo, contraddistinta dalla velleità dei cesaricidi, dagli interessi privati di Marco Antonio, dalla smania di potere di Cesare.